PENGARUH E-WOM, PERSEPSI KUALITAS PRODUK, DAN VARIASI PRODUK TERHADAP KEPUTUSAN PEMBELIAN PRODUK SUNSCREEN AZARINE - Lina Kholi Fitriana; Muhammad Baehaqi (Desanta Publisher, 2026)
This study aimed to examine the influence of e-WOM, perceived product quality, and product variety on purchasing decisions for Azarine sunscreen. A non-probability sampling method was used to select 100 respondents. Data were obtained from a questionnaire and analyzed using instrument validity and reliability tests, classical assumption tests, multiple linear regression, hypothesis testing, and coefficient of determination using IBM SPSS Statistics 26 software. The results showed that e-WOM had no effect on purchasing decisions. Perceived product quality did influence purchasing decisions. Furthermore, product variety influenced purchasing decisions, and e-WOM, perceived product quality, and product variety simultaneously influenced purchasing decisions for Azarine sunscreen